Social Work Core Competencies in Disaster Management Practice: An Integrative Review. (March 2022) - Sim, Timothy; He, Minying; Dominelli, Lena
Purpose: Though social workers are increasingly engaged in the disaster management, there has been a lack of professional guidelines for social work practice and training in this emerging field. This study aims to develop a rudimentary social work competence framework to plug this gap.Method : We conducted an integrative review of 183 international empirical studies and practice reflections, comprising a systematic search, selection, review, and content analysis, guided by ecological systems theory.Results: This rudimentary framework consists of 73 competencies, including 33 micro-level competencies, 18 meso-level ones and 22 macro-level ones, covering knowledge, values and skills in four disaster management phases.Conclusion: Compared to other competence frameworks, this framework further elucidated and classified the salient knowledge, values, and skills in disaster management training and practice for social work.